Electrospun bioactive polymer biomaterials enriched with collagen and platelet-rich plasma as a platform for in vitro chondrogenic differentiation of human mesenchymal stem cells - Trzaskowska, Paulina; Rybak, Ewa; Kopeć, Kamil; Ciach, Tomasz; Wieciński, Piotr; Święszkowski, Wojciech; Kijeńska-Gawrońska, Ewa (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionElectrospun bioactive polymer biomaterials have gained increasing interest as platforms for cartilage tissue engineering due to their ability to mimic the extracellular matrix (ECM) and provide structural and biochemical support for mesenchymal stem cell (MSC) differentiation. The present study aimed to assess the influence of these bioactive compounds on the chondrogenic differentiation of MSCs.MethodsPoly(L-lactic acid) (PLA) fibrous mats were fabricated using electrospinning techniques, including standard and coaxial electrospinning, to incorporate bioactive components, namely collagen I and platelet-rich plasma (PRP). The wettability, the fibers diameter, degradation of the mats and PRP release profile were assessed. MSC differentiation culture was performed to determine the effect of the mats on the chondrogenic lineage.ResultsThe fabricated fibrous mats exhibited distinct morphological and physicochemical characteristics, with core-shell (CS) fibers demonstrating reduced diameters compared to pure PLA and PLA-collagen (Col) fibers. Wettability studies revealed that PRP encapsulation within the PLA shell did not alter the hydrophobic nature of the material, while the presence of collagen significantly enhanced its hydrophilicity. The PRP release profile from CS fibers exhibited a controlled release within the initial 3 days, followed by stabilization. Furthermore, MSC differentiation studies confirmed that both PRP and collagen-enriched fibrous mats supported chondrogenic differentiation over 14-day period, with Col mats demonstrating the highest glycosaminoglycan (GAG) production. The presence of aggrecan, a key chondrogenic marker, was most pronounced on collagen mats and comparable or lower on PRP (CS) compared with PLA, particularly at 14 days.DiscussionFurthermore, the observations revealed the presence of two critical markers of cartilage differentiation: namely, actin cytoskeletal reorganization and depolymerization. The presented findings highlight the potential of bioactive PLA fibrous mats enriched with PRP and collagen I as promising platforms for cartilage tissue regeneration. The combination of electrospinning techniques enables tailored fiber structures that support chondrogenesis, offering a potential alternative for tissue engineering applications.